2018
DOI: 10.1101/358028
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nuclear actin is required for transcription during Drosophila oogenesis

Abstract: Actin influences gene expression at multiple levels. It regulates the activity of specific transcription factors, such as myocardin-related transcription factor (MRTF), is a component of many chromatin remodelers and linked to transcription by all three RNA polymerases (Pol).However, the molecular mechanisms by which actin participates in the gene-specific vs. general transcription have remained unclear. Here we use chromatin immunoprecipitation followed by deep sequencing (ChIP-seq) in Drosophila ovaries to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Beyond its roles in chromatin remodeling complexes, actin has also been linked to different steps of transcription (Fomproix and Percipalle, 2004;Hofmann et al, 2004;Kukalev et al, 2005;Obrdlik et al, 2008;Percipalle et al, 2003), and our recent genome-wide analysis indicates that actin interacts with basically all transcribed genes (Sokolova et al, 2018). In support of this, multiple proteins related to transcription from the assembly of the PIC to Pol II-mediated elongation (Jonkers and Lis, 2015) were identified as high-confidence interactions in our MS screens ( Figure 3A,B, Supplementary table 2).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Beyond its roles in chromatin remodeling complexes, actin has also been linked to different steps of transcription (Fomproix and Percipalle, 2004;Hofmann et al, 2004;Kukalev et al, 2005;Obrdlik et al, 2008;Percipalle et al, 2003), and our recent genome-wide analysis indicates that actin interacts with basically all transcribed genes (Sokolova et al, 2018). In support of this, multiple proteins related to transcription from the assembly of the PIC to Pol II-mediated elongation (Jonkers and Lis, 2015) were identified as high-confidence interactions in our MS screens ( Figure 3A,B, Supplementary table 2).…”
Section: Discussionsupporting
confidence: 57%
“…These findings imply that actin could be directly involved in pre-mRNA splicing/processing. Alternatively, the co-transcriptional nature of splicing (Herzel et al, 2017), and the involvement of actin in transcription (Fomproix and Percipalle, 2004;Hofmann et al, 2004;Kukalev et al, 2005;Obrdlik et al, 2008;Percipalle et al, 2003;Philimonenko et al, 2004;Sokolova et al, 2018), may result in the detection of these RNA splicing/processing related proteins here.…”
Section: Bioid Links Actin To Transcription and Mrna Processingmentioning
confidence: 99%
“…The next fascinating question is whether actin function in gene expression is restricted to the gene level or it impacts the architecture of the genome, seeing the importance of actin in long-range chromosome movement. In favor of a general function of actin in genome regulation, recent chromatin immunoprecipitation and deep sequencing studies have shown that actin binds across both mammalian and Drosophila genomes (Almuzzaini et al , 2016; Sokolova et al , 2018). Indeed, in mouse embryonic fibroblasts where both β-actin alleles are disrupted, we recently discovered that heterochromatin is reorganized.…”
Section: Connecting Gene Expression and Genome Architecturementioning
confidence: 99%
“…Mechanistically, the RanBP9 deletion leads to decreased binding of both actin and Pol II to the chorion genes, which are required for the eggshell formation. 103 The molecular mechanisms by which nuclear actin affects transcription are still largely unclear. In the future, it will be important to decipher these mechanisms in order to understand how nuclear actin dynamics impinges on both gene specific (for example MRTF/SRF and YAP/TAZ-TEAD target genes) and general transcription.…”
Section: Nuclear Actin In Gene Expressionmentioning
confidence: 99%